2022
DOI: 10.3390/genes13091544
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa (HS) is a pathology characterized by chronic inflammation and skin lesions. The molecular basis of the inflammatory network remains unclear; however, since microRNAs (miRNAs) are involved in the modulation of inflammation, the composition of a micro-transcriptome RNA library using the blood of HS patients was analysed here. The total miRNA expression profiles of miRNAs from HS patients was assayed by real-time qPCR. Here, compared to healthy controls, miR-24-1-5p, miR-146a-5p, miR26a-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The main driver of pathogenesis in HS is an overactivation of immune-cell infiltration, which leads to an enhancement of the inflammatory response due to the release of pro-inflammatory cytokines and chemokines. The inflammation may become chronic and, in severe cases, adversely affects diverse tissues and organs ( 33 ). Currently, the etiopathogenesis of HS remains poorly understood due to the complexity and the multifactorial nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The main driver of pathogenesis in HS is an overactivation of immune-cell infiltration, which leads to an enhancement of the inflammatory response due to the release of pro-inflammatory cytokines and chemokines. The inflammation may become chronic and, in severe cases, adversely affects diverse tissues and organs ( 33 ). Currently, the etiopathogenesis of HS remains poorly understood due to the complexity and the multifactorial nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent strides, notably in the work of De Felice et al ( De et al, 2022 ), the exploration of miRNAs within the clinical framework of HS remains at its preliminary stages. While the potential of miRNAs as early detection biomarkers for HS is promising, there are challenges to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by De Felice et al ( De et al, 2022 ) employed conventional molecular techniques to reveal distinctive miRNA expression profiles, notably miR-24-1-5p, miR-146a-5p, miR26a-5p, miR-206, miR338-3p, and miR-338-5p, in HS patients compared to healthy controls. Of particular significance is the overexpression of miR-338-5p in HS lesional tissue, intricately linked to invasiveness and the secretion of pro-inflammatory cytokines; this finding led the authors to postulate its pivotal role in HS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…65 Another study revealed significant differences in the expression of miR-24-1-5p, miR-146a-5p, miR26a-5p, miR-206, miR338-3p, and miR-338-5p in HS. 66 Currently, there is a lack of studies investigating the role of lncRNA in HS. In our study, we performed a comprehensive analysis and successfully constructed a ceRNA network of KYNU specifically for HS.…”
Section: Discussionmentioning
confidence: 99%